2017
DOI: 10.1371/journal.pgen.1006586
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new family of relaxases in Firmicutes bacteria

Abstract: Antibiotic resistance is a serious global problem. Antibiotic resistance genes (ARG), which are widespread in environmental bacteria, can be transferred to pathogenic bacteria via horizontal gene transfer (HGT). Gut microbiomes are especially apt for the emergence and dissemination of ARG. Conjugation is the HGT route that is predominantly responsible for the spread of ARG. Little is known about conjugative elements of Gram-positive bacteria, including those of the phylum Firmicutes, which are abundantly prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 49 publications
10
47
0
Order By: Relevance
“…Multiple oriT regions were identified in over 63% of both the relaxase-typed as well as untyped mobile plasmids, where on average, 2 orits from 2 different Mob groups were identified per plasmid ( Fig 2G). This supported the notion that, besides secondary and in trans oriTs, the untyped plasmids likely carried un-identified relaxases 15,[20][21][22][23][24] . Moreover, the number of Fig 2H).…”
Section: Orit-strast Typing Reveals a Two-fold Increase In The Numbersupporting
confidence: 70%
See 1 more Smart Citation
“…Multiple oriT regions were identified in over 63% of both the relaxase-typed as well as untyped mobile plasmids, where on average, 2 orits from 2 different Mob groups were identified per plasmid ( Fig 2G). This supported the notion that, besides secondary and in trans oriTs, the untyped plasmids likely carried un-identified relaxases 15,[20][21][22][23][24] . Moreover, the number of Fig 2H).…”
Section: Orit-strast Typing Reveals a Two-fold Increase In The Numbersupporting
confidence: 70%
“…The standard approach for characterization of plasmid mobility involves classification of conjugation and mobilization genes 14 , especially typing of relaxase enzymes into the respective mobility groups 15,19 . However, besides the possibility of yet unidentified enzymes and mobility groups 15,[20][21][22][23][24] , multiple new processes have recently been uncovered that might confer additional mobility to plasmids and involve the origin-of-transfer (oriT) DNA substrate. These include (i) broadened relaxase binding specificities to multiple different oriT sequence variants [25][26][27][28][29] , which, according to the evolutionary theory of such DNA regions 4,30,31 , indicates the possibility of plasmids carrying multiple functional secondary oriTs, and (ii) trans-mobilization of plasmids carrying oriTs triggered by relaxases from co-resident plasmids acting in trans on the non-cognate oriTs [32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we found that half of the plasmids (51%) of the COMPASS database are predicted to be mobilizable or self-transmissible. The percentage of mobile plasmid in our study is higher than the one (39%) found by Smillie et al (2010) suggesting that new relaxase and MPF sequences were identified in the last decade (Ramachandran et al, 2017).…”
Section: Characterization Of the Compass Database Using Mob-typermentioning
(Expert classified)
“…The well-documented oriT 110 sequence [20], which is shown in Figure 1, predicted the transfer of the Bs and Spc resistance markers by BEST4305 and BEST4306, respectively, to the recipient BEST386. In the continuous mixing experiment, only the predicted transcipients appeared and increased in number with time ( Figure 4).…”
Section: Transcipients Obtained By Genome Transmissionmentioning
confidence: 85%
“…The pLS20 genes involved in CT activity were identified and categorized as type IV secretion system (T4SS) genes [18,19]. Molecular studies show that the unique CT kinetics involved in pLS20 transmission are regulated by growth-dependent expression of T4SS proteins [18][19][20].…”
mentioning
confidence: 99%